Possible New Syndrome: Left Ventricular Noncompaction, Partial Agenesis of the Corpus Callosum, and Developmental Delay in a Brazilian Child - Lamonica, Dionisia A. C.; Abramides, Dagma Venturini Marques; Maximino, Luciana P.; Gejao, Mariana G.; da Silva, Greyce K.; Ferreira, Amanda T.; Furlan, Renata H.; Giacheti, Célia Maria [UNESP]; Barros-Neto, Plinio A.; Richieri-Costa, A. (Wiley-liss, 2009)
We report oil the clinical, neuropsychological and language characteristics of it boy with left ventricular noncompaction cardiomyopathy (LVNC), agenesis of the splenium of the corpus callosum, minor anomalies of face and limbs, mild mental retardation, and speech and language disabilities. The occurrence of pilomatricoma (calcifying epithelioma) may be part of the clinical spectrum or a fortuitous finding. Compared to other related conditions with LVNC suggests that this is a new unique pattern MCA/MR syndrome. (C) 2009 Wiley-Liss, Inc.
Keywords: left ventricular noncompaction cardiomyopathy; mental retardation; speech/language disorders